Spectroscopic evidence of a particular intermolecular interaction in iodomethane–ethanol mixtures: the cooperative effect of halogen bonding, hydrogen bonding, and the solvent effect. Issue 10 (27th February 2020) - Yao, Fei; Gong, Nan; Fang, Wenhui; Men, Zhiwei
Abstract : The particular intermolecular interaction of an iodomethane–ethanol mixture is revealed by NIR, Raman, DFT calculation, and 2D correlation analysis. Abstract : Halogen bonding, an attractive interaction that is analogous to hydrogen bonding, has been widely investigated by computational methods. However, halogen bonding in solution is hard to study by spectroscopic techniques since the intermolecular interaction often gives overlapping bands and may be difficult to interpret. The traditional interpretation of iodomethane–ethanol mixtures considered only hydrogen bonding effects and the experimental investigation was limited. Here, we employed near-infrared (NIR) spectroscopy, Raman, density functional theory calculation, and two-dimensional (2D) correlation analysis to find evidence of the halogen bonding in iodomethane–ethanol mixtures. Our results suggest that the blue-shifting C–I stretching band is probably due to the cooperative influence from halogen bonding, hydrogen bonding, and the solvent effect, while the O–H band is a cumulative band from three dimer complexes. The 2D correlation spectra further validate the hypothesis above and reveal the interaction evolution from the ethanol-rich region to the iodomethane region. These results indicate that the unique nature of the iodomethane–ethanol mixture and the larger σ-hole strengthen the halogen bond, leading to particular spectroscopic results which are different from those of the other halogenated alkanes.